2018
DOI: 10.20546/ijcmas.2018.709.091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weather Parameters on Population Fluctuation of Sucking Pests and Their Predators on Okra Crop

Abstract: Okra has high nutritional, industrial and medicinal values (Nadkarni, 1927 andChauhan, 1972). It is the rich source of vitamins, minerals like Fe, Mn, Zn, Ni (Bhatt et al., 2018). Medicinally, okra is useful in spermatorrhoea, genito-urinary disorder and chronic dysentery. It also cures ulcers and provides relief from hemorrhoids. The composition of okra pods per 100 g edible portion is: energy 144.00 kJ (36 kcal), water 88.6 g, protein 2.10 g, fat 0.20 g, carbohydrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
3
8
0
Order By: Relevance
“…Chakraborty et al (2014) documented nine species of coccinellids that were associated with insect pests of okra. However, transverse ladybird Coccinella transversalis F, seven spotted ladybird Coccinella septempunctata L and C. sexmaculata were commonly observed (Potai and Chandrakar, 2018;Bhatt et al, 2018;Raghuwanshi et al, 2019;Das et al, 2021); and these results corroborate with the present findings. Pooled data revealed spider (F=119.69; df= 3, 24; p < 0.0001) and coccinellid (F= 338.03; df= 3, 24; p < 0.0001) counts and among the treatment modules there was a highly significant difference (Table 1); spiders remained more or less consistent throughout the crop duration, while coccinellids gradually increased from 25 DAS, reached peak at 65 DAS and again declined to its lowest at 85 DAS.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Chakraborty et al (2014) documented nine species of coccinellids that were associated with insect pests of okra. However, transverse ladybird Coccinella transversalis F, seven spotted ladybird Coccinella septempunctata L and C. sexmaculata were commonly observed (Potai and Chandrakar, 2018;Bhatt et al, 2018;Raghuwanshi et al, 2019;Das et al, 2021); and these results corroborate with the present findings. Pooled data revealed spider (F=119.69; df= 3, 24; p < 0.0001) and coccinellid (F= 338.03; df= 3, 24; p < 0.0001) counts and among the treatment modules there was a highly significant difference (Table 1); spiders remained more or less consistent throughout the crop duration, while coccinellids gradually increased from 25 DAS, reached peak at 65 DAS and again declined to its lowest at 85 DAS.…”
Section: Resultssupporting
confidence: 91%
“…Okra [Abelmoschus esculentus (L) Moench], is an economically important vegetable crop in India which accounts for 72.9% of global okra production (6094.94 mt) and 60% of fresh vegetable export (Anonymous, 2018). Around 17 insect pests have been reported to infest okra (Bhatt et al, 2018a). These include sucking pests such as aphids Aphis gossypii Glover, whitefly Bemisia tabaci (Gennadius), leafhopper Amrasca biguttula biguttula (Ishida) and two-spotted mite Tetranychus urticae Koch and borer pests namely pod borer Helicoverpa armigera (Hübner) and shoot and fruit borer Earias vitella (F).…”
mentioning
confidence: 99%
“…The untreated plot T 10 also revealed maximum number of L. niger (1.72 no./ plant) compared to 0.33 no./ plant with higher dose of chlorantraniliprole + thiamethoxam. Similar findings were recorded by Khan et al (2022) with C. septempunctata and C. carnea Bhatt and Karnatak (2018) also observed more predator from the untreated control plot in kharif season.…”
Section: Resultssupporting
confidence: 89%
“…P. pseudoannulata can attack A. gosypii, A. dugesii, Empoasca sp., Bemisia tabaci (Jiang et al 2020). Coccinellid beetles, such as M. sexmaculatus, are generalist predators that can attack A. gosypii, Empoasca sp., Bemisia tabaci (Bhatt et al 2018). In this study, Aulacophora dorsalis and Aulacophora indica were also found which were the prey of generalist predators.…”
Section: Discussionsupporting
confidence: 56%